The sacred and the secular university - Roberts, Jon H. (Princeton University Press, 2000)
Annotation American higher education was transformed between the end of the Civil War and the beginning of World War I. During this period, U.S. colleges underwent fundamental changes--changes that helped to create the modern university we know today. Most significantly, the study of the sciences and the humanities effectively dissolved the Protestant framework of learning by introducing a new secularized curriculum. This secularization has long been recognized as a decisive turning point in the history of American education. Until now, however, there has been remarkably little attention paid to the details of how this transformation came about. Here, at last, Jon Roberts and James Turner identify the forces and explain the events that reformed the college curriculum during this era. The first section of the book examines how the study of science became detached from theological considerations. Previously, one of the primary pursuits of "natural scientists" was to achieve an understanding of the workings of the divine in earthly events. During the late nineteenth century, however, scientists reduced the scope of their inquiries to subjects that could be isolated, measured, and studied objectively. In pursuit of "scientific truth," they were drawn away from the larger "truths" that they had once sought. On a related path, social scientists began to pursue the study of human society more scientifically, attempting to generalize principles of behavior from empirically observed events. The second section describes the revolution that occurred in the humanities, beginning in the mid-nineteenth century, when the study of humanities was largely the study of Greek and Latin. By 1900, however, the humanities were much more broadly construed, including such previously unstudied subjects as literature, philosophy, history, and art history. The "triumph of the humanities" represented a significant change in attitudes about what constituted academic knowledge and, therefore, what should be a part of the college curriculum. The Sacred and the Secular University rewrites the history of higher education in the United States. It will interest all readers who are concerned about American universities and about how the content of a "college education" has changed over the course of the last century. "[Jon Roberts and James Turner's] thoroughly researched and carefully argued presentations invite readers to revisit stereotypical generalizations and to rethink the premises developed in the late nineteenth century that underlie the modern university. At the least, their arguments challenge crude versions of the secularization thesis as applied to higher education."--The foreword by William G. Bowen and Harold T. Shapiro
Keywords: Universities and colleges -- United States -- History -- 19th century.; Universities and colleges -- United States -- History -- 20th century.; Secularism -- United States -- History.; Humanities -- Study and teaching (Higher) -- United States.; Science -- Study and teaching (Higher) -- United States.; Universités -- États-Unis -- Histoire -- 19e siècle.; Universités -- États-Unis -- Histoire -- 20e siècle.; Sécularisation -- États-Unis -- Histoire.; Sciences humaines -- Étude et enseignement (Supérieur) -- États-Unis.; Sciences -- Étude et enseignement (Supérieur) -- États-Unis.; 81.01 history of teaching.; 15.85 history of America.; EDUCATION -- Higher.; EDUCATION -- History.; Humanities -- Study and teaching (Higher); Science -- Study and teaching (Higher); Secularism; Universities and colleges; United States; Universität; USA; Hoger onderwijs.; Secularisatie (maatschappij); Verenigde Staten.; Colleges and universities -- United States -- History -- 19th Century.; Colleges and universities -- United States -- History -- 20th Century.; 1800-1999; Adams, Charles Francis.; Adams, Herbert Baxter.; Aeneid.; Ancient Greece.; Arnold, Matthew.; Aryanism.; Baconianism.; Bildungsidee.; Bowdoin Theological Seminary.; Carleton College.; Chamberlin, Thomas.; Child, Francis.; Cooke, Josiah Parsons.; Coulter, John M.; Cummings, Edward.; Day, Jeremiah.; Denison College.; Dynamic Sociology.; Eliot, George.; Erasmus.; Folwell, William Watts.; Foster, Frank Hugh.; Genuineness of the Gospels.; Gilman, Daniel Coit.; Gray, Asa.; Hale, William Gardner.; Heeren, Arnold.; Herrick, Clarence Luther.; History of Rome.; Hitchcock, Edward.; Huxley, Thomas.; Illinois College.; Intellectual Science.; Islam.; James, William.; Jay, Martin.; Johns Hopkins University.; Judaism.; Keightley, Thomas.; Kuklick, Bruce.; LeConte, Joseph.; Locke, John.; Marsden, George.; Methodist Book Concern.; Moore, Charles.; National Academy of Sciences.; New York Daily Tribune.; Peirce, Charles Sanders.; Perry, Arthur Latham.; Porter, Noah.; civilization ideal.; nomothetic science.; objectivity: emergence of term.; History